Knowledge and Practices of Patent Medicine Vendors in Rivers State, Nigeria: Implications for Malaria Control in Rural and Sub-Urban Communities - Tobin-West, Charles I.; Adeniji, Foluke O. (Indian Journal of Pharmacy Practice)
Anti-malarial drugs rank high among the drugs administered by patent medicine vendors in Nigeria. Many local inhabitants erroneously perceive these vendors as well knowledgeable on health matters and can be relied on or trusted. This study aims to highlight the knowledge and practices of patent medicine vendors in order to stimulate policy regulation of their practices for effective malaria control and accelerated attainment of the Millennium Development Goals by 2015. A cross sectional study was carried out in October 2008 among 263 patent medicine vendors operating in Rivers State, Nigeria through a two-stage sampling design. All the data generated were analyzed with Epi Info ver 6.04d Statistical Software. Significant tests were performed with confidence level set at 95%. The medicine vendors consisted of 179(68.1%) male and 84(31.9%) female. Most of them had formal education: 148(56.3%) had secondary and 101(38.4%) post secondary education. Their knowledge on the new National Malaria Treatment Policy recommending the use of artemisinin combination therapy for the treatment of uncomplicated malaria in place of monotherapies like chloroquine and sulfadoxine-pyrimethamine was however low (20.5%). Only 24(9.1%) complied with the policy. But their knowledge on use insecticide treated nets was high 250(95.1%). Although most medicine vendors possessed basic education, their knowledge with respect to change in National Malaria Treatment Policy was very low. Adequate dissemination of the new policy and training of patent medicine vendors on rational use of Artemisinin Combination Therapy are necessary to accelerate malaria control in the State and in Nigeria.
Keywords: Patent Medicine Vendors; Malaria Control; Rivers State; Nigeria